Vocabulary size of Malaysian secondary school students / Alice Wong Su Chu ... [et al.] - Wong, Alice Su Chu; Lee, Jocelyn Yee Vun; Fung, Marianne Estabella; Willibrord, Octavia (Akademi Pengajian Bahasa, 2019)
Vocabulary plays a vital role in second language acquisition and is crucial in comprehension of various texts. Without a threshold level of vocabulary proficiency, English Language Learners (ELLs) will have difficulties in processing texts. Indeed, it is well conceded that vocabulary is a good predictor of second language proficiency. While sizable studies have examined ELLs reading skills, little is known about the vocabulary size of Malaysian secondary school students. The current work is part of a larger study that examines the relationship between vocabulary size and critical reading ability. It aims to investigate ELL secondary school students’ vocabulary level and determine whether they are equipped with sufficient vocabulary proficiency for tertiary level education. Eighty-five (85) participants from a public school in Kota Kinabalu, Sabah were involved in the study. A set of receptive vocabulary test was administered during a two-period lesson. Results showed that most of the participants have not mastered vocabulary proficiency beyond the 2000-word level. The findings have pedagogical implications for the teaching of vocabulary at the secondary school level.